Implementasi Penggunaan Media Visual Poster Dalam Pembelajaran Fiqih di SMP Muhammadiyah 47 Sunggal - Sembiring, Eji Habibah; Setiawan, Hasrian Rudi (Yayasan Rahmat Islamiyah, 2024)
This research aims to explore the use of visual media posters in the teaching of Fiqh (Islamic jurisprudence) at SMP Muhammadiyah 47 Sunggal. It employs a qualitative approach, utilizing interviews, observations, and document analysis as data collection techniques. The primary respondents include the School Principal, teachers, and administrative staff. Data analysis techniques that can be utilized include content analysis and qualitative descriptive analysis. Data validity technique employs triangulation, utilizing multiple data sources or collection methods to confirm findings, such as observations, interviews, and document analysis.The research findings indicate that the planning, organization, and implementation of using visual media posters in Fiqh teaching at SMP Muhammadiyah 47 Sunggal have significantly contributed to the enhancement of teaching quality. Thorough planning, as described in Al-Anfal verse 60 of the Quran, is crucial in setting learning objectives and the necessary steps to achieve them.